The effects of massage therapy on weight gain for premature and very low birth weight infants while in the neonatal intensive care unit (NICU) / Musri Kamdar - Kamdar, Musri (2013)
Massage therapy for premature infant can stimulate nerves in the brain which facilitated food absorption, resulting in faster weight gain. It has many benefits for infants, parents, and the hospital. The purpose of this study was to determine the effect of massage therapy on weight gain of premature and very low birth weight (VLBW) infants. Samples were premature and VLBW infants who weighed between 1000 grams and 1500 grams. A total 20 premature and VLBW infants were sampled from the Cipto Mangunkusumo and Islam hospitals in Jakarta, Indonesia. Ten of these infants were designated as the experimental group and ten infants as the control group.The experimental group received massage therapy for 10 to 15 minutes daily for seven days. Massage for the experimental group was tactile and kinesthetic stimulation while the control group was given routine daily care without massage. Data were collected by taking the weights of the infants daily for seven days one hour after morning feed. The result of the study showed that after massage therapy for seven days, the mean weight gain was 112 grams in the experimental group. The infants in the control group had a mean weight gain of 73 grams. Statistically p = 0.03 (<alpha= 0.05), showed that the weight gain of the premature and VLBW infants in experimental group was more significant compared to the infants who only received daily care. Massage therapy for premature and VLBW infants indirectly improve weight gain of the infants.